Variability and early selection for tea plant population derived from artificial crossings - Heri Syahrian Khomaeni; Bambang Sriyadi (Jurnal Penelitian Teh dan Kina, 2011)
The purpose of tea breeding is to develope new elite clones. Artificial crossings is the method for developing a new population with high genetic variability in respective traits followed by selection process. Genetic variability information is important in selection method. A hundred and five F1 plants were planted in 1991. These F1 plant were selected from F1 generations of several parental cross combinations between PS 1, PS 354, TRI 777, TRI 2024, TRI 2025, Kiara 8, KP 4, and Cin 143. The crosses were made in 1989. Observed variables were yield per bush, number of pekoe, number of dormant shoot (banji), weight of p+3 (pekoe with three leafs below), weight of p+2 (pekoe with two leafs below), and weight of banji. Phenotypic variance and standard deviation were made. The level of variability of all characters were evaluated. All plants with performance level greater than general mean plus one and a half standard deviation were selected for respective traits. Results showed that yield per bush, number of pekoe, and number of banji had wide variability. The variability of p+3, p+2, and banji had narrow variability. Eight bushes were selected with yield potential ranging from 4,290 kg/ha/year and 6,261 kg/ha/year.